An improved longitudinal failure criterion for UD composites based on kinking model. Issue 6 (28th February 2022) - Chen, Xiangming; Sun, Xiasheng; Wang, Binwen; Gu, Jiefei; Zou, Peng; Chai, Yanan; Yang, Junchao
Abstract: A longitudinal failure criterion for UD composites based on a kinking model was re-constructed guided by the principles of analytic geometry. The proposed method for determining the fiber initial misalignment angle considers the shear nonlinear response of the matrix. An expression accounting for the fiber matrix coupling failure was used to simulate shear-driven fiber compression failure. Different effects of the matrix shear on the fiber tensile and compressive failure was considered. Compared with the kinking model, the proposed criterion better predicted the compression failure mode, gave better agreement with the experimental results, and exhibited better adaptability for different fiber failure modes.